(untitled) (Faridpur Medical College Journal, 2015)
To determine the factors related with depression among adolescent students, 165 male adolescent students aged 15 to 19 years from 2 urban schools and colleges were interviewed with semi-structured questionnaire during January to June 2012.The socio demographic details, smoking and depression histories were recorded. The Center for Epidemiologic Studies Depression Scale (CES-D) was used to measure the presence of depression. Smoking behavior was measured by a number of questions. Almost 49% respondents were depressed and 66% were smokers. Most of the respondents started smoking around the age of 14.3 years (54.1%) by the influence of their friends. Among the smokers 82.7% were depressed while 17.3% were depressed among nonsmokers (?2=19.69, p=<0.001). Parental smoking affected 62.5% respondents for depression against 59.4% normal respondents whose parents were non smokers (?2=7.52, p=.006). Domestic violence (?2=18.4, p=<0.001), familial disharmony (?2=18.44, p=0.001), stressful events in the life (?2=21.38, p=<0.001), failure in love (?2=12.6, p=0.002) also played roles for depression. After adjusting the non significant factors in logistic regression, familial disharmony (p<0.001), smoking (p=0.005) and stress (p=0.04) became significant factors associated with depression. Depression level was higher among adolescent smoker than nonsmoker students. Faridpur Med. Coll. J. 2014;9(2): 73-75